Blue fluorescence from N, O-coordinated BF2 complexes having aromatic chromophores in solution and the solid state. Issue 12 (27th November 2019) - Yamaji, Minoru; Tomonari, Kazuhiro; Ikuma, Keisuke; Goto, Kenta; Tani, Fumito; Okamoto, Hideki
Abstract : N, O -Coordinated BF2 complexes (Ar@HCs) having aromatic (Ar) and heterocycle (HC) moieties were prepared, and their photophysical properties were investigated in solution and the solid state along with their crystal structures. Abstract : We prepared amide-heterocycle (HC) compounds having various aromatic π-electron systems (Ar), such as phenyl, naphthyl, furyl, thienyl and phenanthryl moieties, and converted them as ligands to difluoroboronated complexes, Ar@HCs. Blue fluorescence from Ar@HCs was observed in solution and the solid state, and the fluorescence quantum yields ( Φ f ) and lifetimes ( τ f ) were determined. The Φ f values in CHCl3 were as small as 0.1 except for the phenanthrene derivatives (0.4–0.6). Observation of the triplet–triplet absorption upon laser flash photolysis of Ar@HCs in solution indicated that the fluorescence process competes with intersystem crossing to the triplet state. Blue fluorescence in the solid state was observed with the Φ f values of 0.3–0.7. Based on the crystallographic data, the relationship between the crystal structures and emission features of Ar@HCs in the solid state is discussed.